Worms and Human Disease. - Muller, Ralph, 1933- (CABI, 2001)
The second edition of this advanced student textbook has been thoroughly updated and revised since it was first published in 1975. It covers all human helminth infections with particular emphasis on diagnosis, treatment, clinical manifestations, pathogenesis, epidemiology and control.